2001
DOI: 10.1162/152638001317146363
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and the Oil Industry: Common Problems, Different Strategies

Abstract: The primary focus of most academic climate policy studies has been the robustness of climate science and the development of international negotiations and institutions, in which states, and sometimes societies, have been pinpointed as the key players. Systematic comparative studies of multinational and even global non-governmental actors have been in short supply. This research lacuna is particularly glaring since the position of a major non-state actor-the oil industry-may be crucial to the viability of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 8 publications
1
61
0
Order By: Relevance
“…Early studies have examined the attitudes and strategies of major global oil companies toward the tradeoff between profitability and carbon emissions [1,2,9,10], typically based on case studies. The main finding is that the major multinational oil companies have adopted very different strategies, and the divergence can be caused by corporate-specific factors and varying stakeholder pressures.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies have examined the attitudes and strategies of major global oil companies toward the tradeoff between profitability and carbon emissions [1,2,9,10], typically based on case studies. The main finding is that the major multinational oil companies have adopted very different strategies, and the divergence can be caused by corporate-specific factors and varying stakeholder pressures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Business leaders, policymakers and researchers have reached a consensus that limiting the carbon emissions from the oil and natural gas industry is an important task in coping with the challenge of climate change [1,2]. Consequently, the industry has undergone a lot of pressures to take actions to mitigate the carbon emissions [3].…”
Section: Introductionmentioning
confidence: 99%
“…The sharp contrast in target stringency is a reflection of the significant difference in the strategies adopted by the companies in the two regions in response to climate change. The literature has shown that the oil and gas companies in the EU have taken more proactive policies, while the US companies have adopted more reactive strategies [28]. The proactive policies of the EU firms may drive them to set more aggressive targets.…”
Section: Target Stringencymentioning
confidence: 99%
“…The proactive policies of the EU firms may drive them to set more aggressive targets. The reasons for the difference in climate strategies of the oil and gas firms may be found in the political, regulatory and societal contexts [28]. The Materials sector in the EU set significantly more stringent targets than the US (p < 0.01).…”
Section: Target Stringencymentioning
confidence: 99%
“…What little analysis exists of the consequences of climate change for the petroleum sector is mostly from the early 2000s, with a peak around 2002 Springer, 2002;Van den Hove, Le Menestrel, and de Bettignies, 2002;Le Menestrel, van den Hove, and de Bettignies, 2002;Skjaerseth and Skodvin, 2003;. Given the fast pace of change in the petroleum sector, in climate science and in climate politics, much of this literature is now outdated.…”
Section: Climate Policymentioning
confidence: 99%